2004
DOI: 10.1086/386537
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐Ray Emission Properties from Mature Pulsars in the Galaxy and in the Gould Belt

Abstract: We study the -ray emission properties of pulsars by using a new self-consistent outer gap model. The outer gap can exist in pulsars older than 1 million yr if the effect of magnetic inclination angle, as well as the average properties of the outer gap, are considered. The mature -ray pulsars, whose ages are between 0.3 and 3 million yr, are able to move up to high Galactic latitude. Moreover, their -ray luminosities are weaker, and their spectra are significantly softer than those of younger -ray pulsars in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 43 publications
1
27
1
Order By: Relevance
“…However, since their simulation accounts for only $1/4 of the total unidentified -ray population, the hypothesis that all of the sources are pulsars would suggest that $15 radio-loud pulsars ought to have been detectable in our sample of EGRET sources. A similar study by Cheng et al (2004), based on the outer gap emission model, finds $4 radio-loud pulsars from the Gould Belt and another four from the remainder of the Galaxy at jbj > 5 . The total number of pulsars at midlatitudes from this simulation accounts for $1/2 the total unidentified population, indicating that our survey should have detected $8 associated radio pulsars.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, since their simulation accounts for only $1/4 of the total unidentified -ray population, the hypothesis that all of the sources are pulsars would suggest that $15 radio-loud pulsars ought to have been detectable in our sample of EGRET sources. A similar study by Cheng et al (2004), based on the outer gap emission model, finds $4 radio-loud pulsars from the Gould Belt and another four from the remainder of the Galaxy at jbj > 5 . The total number of pulsars at midlatitudes from this simulation accounts for $1/2 the total unidentified population, indicating that our survey should have detected $8 associated radio pulsars.…”
Section: Discussionmentioning
confidence: 69%
“…This luminosity limit is lower than the 1400 MHz luminosity of all but two pulsars for which this quantity has been measured and published (Manchester et al 2005). 12 The surveys used for the studies mentioned above were typically $4 times less sensitive than our survey (assuming an average spectral index of À2 for pulsars, as was assumed by Cheng et al 2004). Our results suggest that the simulations significantly overestimate the radio-loud -ray pulsar population at midlatitudes and do not support the hypothesis that middle-aged, nearby pulsars make up the majority of the unidentified sources.…”
Section: Discussionmentioning
confidence: 72%
“…The basic procedure of the Monte Carlo method and the evolution of pulsar parameters are described in our previous works Zhang & Cheng 1999;Zhang et al 2000Zhang et al , 2004Cheng et al 2004). We have made two improvements in our Monte Carlo simulation: (i) Parkes 70 cm survey and Princeton NRAO survey data are used and (ii) the distance model of Cordes & Lazio (2002) is used to estimate the dispersion measure of the simulated pulsars.…”
Section: Monte Carlo Simulation Of γ-Ray Pulsarsmentioning
confidence: 99%
“…Based on the polar cap models, Harding & Zhang (2001) suggested that the off-beam γ-rays come from high-altitude curvature emission of primary particles and can radiate over a large solid angle and have a much softer spectrum than those of the main beams, and at least some of radio-quiet Gould belt sources detected by EGRET could be such off-beam γ-ray pulsars. In the framework of the outer gap model, Cheng et al (2004) investigated the emission properties of γ-ray pulsars in Galaxy and in the Gould belt.…”
Section: Introductionmentioning
confidence: 99%
“…The thresholds of EGRET and GLAST included in Fig. 3 were taken from Cheng et al (2004) and McEnery et al (2004). With the high sensitivity of GLAST, which will be launched at the end of 2007, we should be able to detect the increase in gamma-ray flux.…”
Section: Discussionmentioning
confidence: 99%